Tragsessel in europäischen Herrschaftszentren Vom Spätmittelalter bis Anfang des 18. Jahrhunderts - Döberl, Mario (2020)
For the first time ever, the present anthology deals in depth with the early age of the sedan chair in Europe, in other words, the period between the late Middle Ages and the beginning of the 18th century. It comprises seven essays by international researchers describing the introduction and establishment of the sedan chair in various different European centres of power. The contributions focus on developments at the papal court, in Genoa, in the Spanish monarchy, at the Viceregal Court of Naples, at the courts of the Austrian Hapsburgs, at the Bavarian court, and in France.